Student Entrepreneurial Intention Based on Proactive Personality, Self-Efficacy and Anticipatory Entrepreneurial Cognitions - Dedek Kurniawan Gultom; Muhammad Arif; Willy Yusnandar; Radiman Radiman (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to produce a Model Construction of Student Entrepreneurial Intentions Based on Proactive Personality, Self-Efficacy, and Anticipatory Entrepreneurial Cognitions. While the specific objective is to identify the factors that influence Student Entrepreneurial Intentions and generate Model Construction of Student Entrepreneurial Intentions Based on Proactive Personality, Self-Efficacy, and Anticipatory Entrepreneurial Cognitions. The population used in this study were students of the Faculty of Economics and Business from several of the best Islamic tertiary institutions in the city of Medan with the criteria that these universities have an Islamic vision and mission, and have a business incubator center or entrepreneurship center. The data analysis technique used in this research is descriptive analysis, both qualitative and quantitative. Data analysis with statistics used is Structural Equation Modeling with data processing using LISREL 8.80 software. The results of the study show that the Active Personality variable has a significant positive effect on Self-Efficacy. Active Personality Variable has a positive effect on Entrepreneurial Intentions significantly. Self-Efficacy Variable has a significant positive effect on Anticipatory entrepreneurial cognitions. The Self-Efficacy variable has a significant positive effect on Entrepreneurial Intentions. The anticipatory entrepreneurial cognitions variable has a significant positive effect on Entrepreneurial Intentions